2013
DOI: 10.1159/000348320
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Spinal Cord Disorders in Al-Quseir City, Red Sea Governorate, Egypt

Abstract: The knowledge of the prevalence of spinal cord disorders (SCD) is important to understand specific causes in each part of the worldand to allow to potentially adapt health care and public policy including law enforcement to the main causes. SCD have important personal, biopsychological, socio-economic, short-term and long-term consequences. An SCD is the underlying cause for 1 of every 40 patients admitted to a major trauma centre. The affected population consists primarily of young male adults. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
4
0
2
Order By: Relevance
“…High education was recorded in only 5% of the patients. This is in agreement with many previous studies, which showed that the prevalence of AD is more in illiterate people than educated ones [19][20][21][22]. However, this is not in agreement with the results of Ghuloum and colleagues [23], who reported that there in no significant association between education level and dementia in a Qatari population.…”
Section: Discussionsupporting
confidence: 74%
“…High education was recorded in only 5% of the patients. This is in agreement with many previous studies, which showed that the prevalence of AD is more in illiterate people than educated ones [19][20][21][22]. However, this is not in agreement with the results of Ghuloum and colleagues [23], who reported that there in no significant association between education level and dementia in a Qatari population.…”
Section: Discussionsupporting
confidence: 74%
“…Among included studies, 37 were retrospective, 8 were prospective, and two studies were cross-sectional [54, 71]. Only four studies were population-based [28, 36, 46, 70], while 14 and 29 were hospital-based and rehabilitation-based, respectively. Although the Egypt study by Tallawy et al [36] only included six TSCI patients, we had it in our study because it was a population-based door-to-door study among all city citizens.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies were population-based [28, 36, 46, 70], while 14 and 29 were hospital-based and rehabilitation-based, respectively. Although the Egypt study by Tallawy et al [36] only included six TSCI patients, we had it in our study because it was a population-based door-to-door study among all city citizens. Its results were acquired by an extent valuable screening.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-one studies 10,11,[24][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40]42,43,[45][46][47]50,52,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][74][75][76]78,[80][81][82][83][84][85][86][87]…”
Section: Overall Prevalence Of Yodunclassified